FasL Promotes Proliferation and Delays Differentiation of ASCs. Issue 1 (2021) - Sarel, Ina; Or, Ela Bar; Ben-Yehudah, Ahmi; Solodeev, Inna; Shani, Nir; Yarkoni, Shai; Rodionov, Galina; Ofer, Amos; Rosenzwaig, Michal; Tzadok, Michal Shrift; Rodin, Anastasia
No abstract available